Clay-shale materials as low-cost landfill liners: an integrated geochemical and geotechnical assessments (2015)
Increasing rate of wastes generation due to urbanization and industrialization, as well as the need for proper waste disposal management has been the concerns of many low income countries like Nigeria. Hence, this study assessed the geotechnical and chemical characteristics in respect of suitability of selected clay-shale deposits in Nigeria as low cost landfill liners for waste disposal. Twenty four (24) clay-shale samples were subjected to engineering tests, mineralogical XRD and geochemical analyses. Apart from normal kaolinitic clay, the XRD analyses revealed smectitic and mixed layer clays with Liquid Limit (LL) of 58.3 – 116.5 (av. 75.4) and 170.4 – 173.2 (av. 171.8) respectively while the Plasticity Index (PI) ranged from 20.3 – 51.6 (av. 31.8) and 80.9 – 93.3 (av. 87.1) respectively. Methylene blue adsorption index (MBI) ranges from ≈10 to 18.6 meq/100g for both smectictic and mixed layer clay-shales with corresponding surface area of 0.8−1.5m2/g, suggesting the dominance of active clay minerals. In addition, the geochemical analyses show that the clay-shale materials contain significant amount of Al2O3 with average value of 17.0 and 15.9% respectively while Fe2O3 has average value of 8.2 and 6.5% respectively, suggesting Fe-rich smectitic clays. The overall evaluation revealed that the clay-shale materials are chemically and geotechnically suitable for application as landfill liners subject to appropriate beneficiation /amendment such as mixing with cement and other binding materials.